Child Language Acquisition: A Study of Phonological Aspects in Children Aged 3-5 Years at Paud Tanwirul Hija Cangkreng Lenteng Sumenep - Nalini, Sitti Nurfaiqoh; Hodairiyah, Hodairiyah; Nurhayati, E.A.A. (SAINTIS Publishing, 2025)
This study aims to describe the process of acquiring vowels and consonants in children aged 3-5 years at PAUD Tanwirul Hija Cangkreng Lenteng Sumenep. Data is in the form of words that contain vowel elements and consonants. Data collection is carried out through documentation and observation techniques. Data analysis was carried out qualitatively with a focus on the pronunciation of vowel and consonant sounds, as well as children's ability to use these sounds in the context of daily communication. The results of the study showed that children aged 3-5 years at PAUD Tanwirul Hija had mastered all basic vocal sounds well. Mastery of consonant sounds shows varied, but generally positive, results, with some children having difficulty pronouncing certain consonants. In conclusion, children at PAUD Tanwirul Hija showed good development in language acquisition, with articulation skills that were appropriate to their developmental stage. Interaction with parents and the environment contributes significantly to this language acquisition process.